PENERAPAN LEAN MANAGEMENT DALAM PROSES PERSALINAN UNTUK EFISIENSI DAN KESELAMATAN PASIEN - Sri Rahma Friani; Meli Safreni Turnip; Adventides Natali Siahaan (Jurnal Minfo Polgan, 2022)
The birth process, although a natural event, often involves a series of complex workflows that can potentially generate waste and risks to the safety of mothers and babies. Lean Management, a management philosophy focused on eliminating waste and creating value, has proven effective across various industries, including healthcare. This literature review aims to explore the application of Lean Management in the birth process, analyzing its impact on operational efficiency and patient safety. The review results indicate that the application of Lean principles such as value identification, value stream mapping, continuous flow, pull systems, and continuous improvement (kaizen) can reduce waiting times, medical errors, costs, and increase patient and staff satisfaction. Implementation challenges include resistance to change, training needs, and leadership commitment. The integration of Lean Management can optimize the birth process, making it more efficient, safe, and patient-centered.